Analisis Winding Insulation Pada Performa Induksi Motor Tiga Phase Berbasis Logika Fuzzy - Fajar Pujiyanto (Sekolah Tinggi Maritim Yogyakarta, 2022)
The three-phase induction motor is the best option for driving machinery in the industrial world, it was chosen because of its reliability and easy maintenance. Maintaining the performance of induction motors is important to avoid motor malfunctions and maintain industrial production. The performance degradation is due to mechanical, electrical, and environmental influences. Detecting problems early is necessary for repairs to be carried out as soon as possible to avoid further damage. The cause of failure in the winding is influenced by the value of the insulation resistance. Factors causing changes in the IR value are electrical stress, mechanical stress, chemical stress, thermal stress, and environmental contamination. This study discusses the analysis of the performance of the induction motor by the value of insulation deterioration, namely the value of insulation resistance (IR), polarization index (PI) and relative humidity (RH), this is important because the low value of the three components causes a decrease in performance and failure of the induction motor Keywords: Fuzzy logic, Induction motor, Performance, Winding insulation.